Connecting Gratitude and Self-Efficacy in Food Waste Reduction: A Conceptual Perspective on Social Marketing in Indonesia - Widayanti, Ipuk; Hanung Eka Atmaja; Yesica Apriliana Paska; Satrio Tegar Sadewo (LPPM Universitas Terbuka, 2024)
This paper examines the critical global issues of food insecurity and food waste, with a specific focus on Indonesia, a country that ranks second among the top 25 contributors to food waste. Despite being a significant contributor to global food waste, Indonesia faces a paradoxical challenge of widespread hunger, with millions of its population experiencing food insecurity. The 2030 Sustainable Development Goals (SDGs) highlight the urgent need for awareness and action to reduce food waste, yet empirical research on food waste behavior, particularly at the household level in Indonesia, remains scarce. Existing studies predominantly utilize theoretical frameworks such as the Theory of Planned Behavior (TPB) to analyze food waste behavior, though these are primarily exploratory in nature. This paper identifies a gap in empirical research and presents an opportunity to investigate food waste behavior in Indonesia using contextual data. Drawing on the perspective of social marketing, the paper also reviews recent studies, including those by Kim et al. (2020), which explore the effectiveness of social marketing programs in promoting food waste reduction. Furthermore, it considers the role of emotional factors, such as gratitude, in influencing consumer behavior toward food waste, as discussed in research by Septianto et al. (2020). The paper concludes by highlighting the potential policy instruments and interventions suggested by Principato et al. (2021) that can contribute to reducing food waste at the consumer level. Through this conceptual framework, the paper aims to foster greater understanding of food waste issues in Indonesia and provide insights for future empirical research and policy development.